Optimization of beef broth processing technology and isolation and identification of flavor peptides by consecutive chromatography and LC‐QTOF‐MS/MS. Issue 8 (26th June 2020) - Wang, Linhan; Qiao, Kaina; Huang, Yan; Zhang, Yuyu; Xiao, Junfei; Duan, Wen
Abstract: To investigate the flavor peptides of beef broth obtained under optimized stewing conditions, separation procedures such as ultrafiltration, Sephadex G‐15 column chromatography, and reversed‐phase high‐performance liquid chromatography were employed to isolate the umami taste peptides. Sensory evaluation was combined with liquid chromatography–mass spectrometry to detect the flavor peptides. The optimization of the stewing process conditions was studied using the orthogonal method, which indicated that time had the most significant effect on the taste efficiency of sensory evaluation, followed by the mixed spices, sucrose, and salt. The optimized cooking conditions included 3.5 hr of cooking time, 1.800 g of sucrose, 2.125 g of salt, and 1.500 g of mixed spices. The results showed that six peptides, including SDEEVEH, AEVPEVH, GVDNPGHP, GSDGSVGPVGP, SDGSVGPVGP, and DEAGPSIVH, were detected in sample X1M1; and seven peptides, including VAPEEHPT, VVSNPVDIL, VGGNVDYK, PFGNTHN, EAGPSIVHR, VDFDDIQK, and DEAGPSIVH, were detected in sample X2M2. This study compared the flavor peptides in stewed beef before and after the optimization, and thus provided a basis for the improvement of beef processing technology. Abstract : Sensory evaluation combined with liquid chromatograph quadrupole time‐of‐flight mass spectrometry/mass spectrometry to separate flavor peptides. The optimal stewed beef formula was obtained by sensory evaluation. The results showed that six peptides were detected in sample X1M1; and seven peptides were detected in sample X2M2.